Navigating precarity in everyday (sub)urban space in Helsinki, Finland - Jaatsi Mia; Kymäläinen Päivi (WILEY, 2025)
This article addresses the everyday forms of urban precarity, which is under-studied in the context of Finnish cities. We examine how urban precarity becomes lived, practiced, and resisted in the case of a suburban open-air shopping center in Helsinki, Finland. Referring to precarity as a socio-spatial condition that reveals the precariousness of urban people and places, this study discovered everyday forms of urban precarity in detailed materialities and tactics; in housing, food, and addiction struggles; and in movements and networks. These mundane manifestations revealed that precarity could be approached in more relative terms that are not linked with certain neighborhoods but that emerge as spaces with intersecting nodes of services, networks, mobilities, and sociality. We conclude that particular places across urban spaces, where these aspects intersect, can be central to the ways precarity is navigated in the city and to increasing understandings of the mechanisms through which spaces of precarity are constructed in the city. The methodological choices used in this article-volunteer ethnography and vignettes-present profound accounts of the microscale lived experience, and bring humanness to a context that often exhibits stereotypes and marginality.